't Knalpotteke ; Knalpot. (Antwerpen : Atthis, 1979)
Fonds Suzan Daniel (FSD)
Vanaf 01(1979-80) 5: Knalpot
Periodiciteit : tweemaandelijks
Redactie : Burgemeester Woutersstraat 5, 2600 Berchem ; vanaf 01(1979-1980) 7 : Verbondstraat 53, 2000 Antwerpen ; vanaf 14(1991-1992) 1 : Volksstraat 7, 2000 Antwerpen ; vanaf 19(1996-1997) 4 : Geuzenstraat 27, 2000 Antwerpen
Nederlands
Periodiek
Keywords: lesbische vrouwen